Perancangan Interior Kidzania Mini di Malang Town Square - Jessica Christina Sugianto; Sherly de Yong; Lucky Basuki (Intra, 2019)
Early age is the most appropriate age for a child to develop their imagination in learning new things, but not many parents are able to see and take advantage of that moment.City of ‘Education’ as an image of the Malang City is the main reason for this design to be presented in the Malang City, so that children can be educated on the world of profession by playing. For this reason, a place like Kidzania Mini is needed in Malang Town Square that is able to present a professional experience for children aged 4 to 16 years with a smaller area.Design Thinking method was used as design guideline with the steps of understand, observe, point of view, ideate, prototype, and test. The basic concept of Kidzania Mini is a city park surrounded by profession buildings with a touch of Kidzania's character. The application of the character Kidzania is applied to profession spaces as well as statues and other decorations in the garden of the Kidzania City.